Rice Field Necessity to Sufficient Production of Food Material - RITUNG, SOFYAN (Jurnal Sumberdaya Lahan, 2010)
Indonesian population from year to year increasing, with growth of about 1.5%/year, thus pushing food demands continues to increase. Particularly agricultural land especially rice field, covering an area in 2005 reached 7.89 million hectares was not able to meet the food needs of Indonesia, so that needs to be supplemented by imports which in the last decade it has increased. The need for food began to increase and in the year 2020 deficit is estimated to occur if there is no additional production of 1.1 million tons of rice or equivalent to 1.8 million tons of GKG. In 2050 demand for rice will reach 48.2 million tons, an increase of 145%. Commodity corn and soybeans are expected to occured a deficit each of 2.2 million tons and 2.5 million tons in 2050. To sufficient the necessity of food until the year 2050, assuming that the conversion of rice land could be reduced to 60,000hectares/year, required the new rice fields of about 1,6-2,4 million hectares in 2020 and the cumulative area until the year 2050 is 6.0 million hectares.The potential availability of land for extensification of rice field in Indonesia is 8.28 million hectares, consists of 2.98 million hectares swamp rice field and 5.30 million hectares of non swamp rice field. The largest potential development are in Papua, Kalimantan, and Sumatra, each of 5.19 million hectares, 1.39 million hectares, and 0.96 million hectares. Rice field extensification strategies can be done through land use potential rice fields in the irrigation areas, abandoned rice field optimization in the tidal swamp and inland swamp, and extensification of rice field region scale in area large potential like Papua and Kalimantan.